2020
DOI: 10.19102/icrm.2020.111002
|View full text |Cite
|
Sign up to set email alerts
|

Leadless Pacemaker Implantation in a Four-year-old, 16-kg Child

Abstract: Leadless pacemakers have an accepted role with demonstrable benefits in adults. In contrast, implant experience and follow-up data in pediatric patients are more limited. Clinical indications and patient candidacy for leadless pacing in pediatrics continue to evolve. We present our experience implanting a leadless pacemaker in a four-year-old for the treatment of high-grade atrioventricular block. Implant considerations in small patients, short-term patient and device follow-up data, and follow-up assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…7 This hybrid approach, with their systematic approach to vessel assessment with preprocedural ultrasound imaging nicely described in the article, is contrasted with the femoral vein approach, which has been used in patients as small as 16 kg. 8 It has been suggested that a minimum vessel diameter of 9 mm is required for the 27-French (Fr) delivery sheath, though the distensibility of the femoral vasculature has been demonstrated by proponents of the traditional femoral approach in even the smallest patients (Figure 1).…”
Section: Leadless Pacemakersmentioning
confidence: 99%
“…7 This hybrid approach, with their systematic approach to vessel assessment with preprocedural ultrasound imaging nicely described in the article, is contrasted with the femoral vein approach, which has been used in patients as small as 16 kg. 8 It has been suggested that a minimum vessel diameter of 9 mm is required for the 27-French (Fr) delivery sheath, though the distensibility of the femoral vasculature has been demonstrated by proponents of the traditional femoral approach in even the smallest patients (Figure 1).…”
Section: Leadless Pacemakersmentioning
confidence: 99%
“…2,3 Despite these drawbacks, leadless TPSs have been used in carefully selected pediatric patients, often motivated by limited venous access, risk factors for endovascular infection, and/or anticipated time-limited pacing need. [4][5][6][7][8][9] In this issue of The Journal of Innovations in Cardiac Rhythm Management, Hackett et al report the implantation of a Micra™ VR TPS in a 28 kg, nine-yearold patient by surgical cutdown of the right internal jugular vein.…”
Section: Drs Beach and Vinocur Discussmentioning
confidence: 99%
“…In this particular case, leadless pacing was considered a firstline treatment option in an individual without contraindications to traditional transvenous or epicardial implant approaches. Previous publications [8][9][10][11][12][13] have cited limitations to conventional implants due to patient-related circumstances or medical complexities, thereby driving the decision to pursue leadless pacing as a secondary option.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leadless pacemakers pose an interesting and novel solution for many pediatric patients. However, other than a handful of case reports and case series' the majority of cases have been performed in adults 2,3,6–9 . A major disadvantage of the leadless pacing approach is the large size of the delivery sheath (27‐French outer diameter), which can be prohibitive in small patients.…”
Section: Introductionmentioning
confidence: 99%